Performance analysis for cooperative NOMA networks based SWIPT with adaptive power splitting - Zheng YANG; Yun ZHENG; Yuehao YU; Yi WU; Zhicheng DONG; Song XING (Tongxin xuebao)
In order to improve the spectrum effectiveness, decrease the power consumption of wireless communication system, for a two-way cooperative non-orthogonal multiple access (NOMA) network with simultaneous wireless information and power transfer (SWIPT), an adaptive power splitting scheme of SWIPT was proposed.Based on the decode-and-forward protocol and the users’ distance information, the successive interference cancellation was carried out at the relay to decode the users’ messages and harvest the energy from the sources.An adaptive power splitting scheme was proposed based on users’ channel state information, which the relay could successfully decode the users’ information and harvest the most energy from the sources.Based on the harvested energy, the relay forwarded the decoded information of the users in the next time slot.According to the proposed adaptive power splitting scheme, the overall outage probability, end-to-end outage probability, and the diversity gain at high signal-to-noise ratio were derived.Compared with three-way cooperative orthogonal multiple access network with fixed power splitting of SWIPT, the proposed adaptive power splitting of SWIPT for two-way cooperative NOMA networks can achieve much better outage performance.